Exploring Student Perspectives of Project-Based Learning in an Agricultural Communications Capstone Course - Lyndsay M. Burmesch; Bradley M. Coleman; Audrey E. H. King; Shelly Legg; D. Dwayne Cartmell II (Journal of Applied Communications, 2024)
Capstone courses can foster skills like teamwork, communication, and interpersonal skills, and project-based learning can be an effective approach to such courses. This study explored students’ perceptions and experiences of a project-based learning approach in an undergraduate, capstone, agricultural communications course. Using a convergent mixed-methods design, an end of course questionnaire was administered, and post-course focus groups were conducted. The highest scored item was ‘I was satisfied with the level and quality of communication I had with the instructor.’ The lowest scored item was ‘the course helped me develop a deeper appreciation for the subject.’ Qualitatively, two overarching themes emerged: (a) project-based learning: “I can do this. I did this,” and (b) realistic application: an invaluable foundation. The first theme included four sub-themes: (a) critical thinking: “trial by fire,” (b) feedback … “is really critical,” (c) pride and effort: “we’re making a freaking magazine,” and (d) project fatigue: “it’s hard to not have an attitude.” The second theme included two sub-themes: (a) collaboration: balancing “so many personalities,” and (b) burnout and stress: “a million little things.” The findings of this study further support the use of PBL in higher education. The course provided preparation for post-graduation endeavors, with students recognizing the transferability of skills across career paths. While students discussed experiencing project fatigue, instructors may mitigate stress by establishing clear expectations, providing a schedule and deadlines, and providing assistance. Additional research exploring project-based learning in agricultural communications settings is needed to offer deeper insights regarding student learning outcomes.
Keywords: college teaching; project-based learning; capstone course; agricultural communications; mixed methods